Characteristics of lyrical melodies have The artist Talib Al-Qargholi - Shah Murad, Saeed Mahdi; Jassim, Firas Yassin (Al-Adab Journal, 2021)
Singing is one of the prominent artistic features in Iraq, and the city of Baghdad in particular, in which many colors and singing experiences have emerged and crystallized in different periods of time, especially the seventies of the twentieth century, being an important and distinctive era in the Iraqi song’s march in which it reached the height of melodic and performance formulation. The hand of a distinctive constellation of composers, including the artist (Talib Al-Qargholi), Which is considered one of the most prominent contributors to the development of the song and the enrichment of its artistic career, and despite the importance of his works, they did not study a specialized scientific study, and this research is concerned with studying it by revealing the characteristics of the lyrical melodies of this artist. The importance of research is highlighted by the new knowledge it adds, shedding light on the career of a distinguished artist and the characteristics of his lyrical music, as well as providing new information and opinions as a new source added to the Arab library in general and the Iraqi library in particular. The research reviewed the Iraqi song and its stages of development in the twentieth century. It also talked about the life of the artist Talib Al-Qargholi and his role in the Iraqi song. The research examined samples chosen in a random manner that represented the community represented by the songs composed by the artist Talib Al-Qargholi, by analyzing them with a standard designed for this purpose, to come to a set of results and conclusions, the most prominent of which is the diversity in the Maqam scales that he uses, especially the common ones in Arab and Iraqi music and singing, with Moving to other nearby stairs, of a purely local character, which indicates the expansion of the Maqamid diversity, as well as the distinctive melodic density of his works.